Strategic plans to support action against climate change in the Arab countries in the Middle East Region - Danish, Mohammad; Isaifan, Rima J. (Journal of Sustainable Development Law and Policy, 2025)
Climate change has become a global challenge due to its critical impact on the natural as well as the human environment. This article focuses on the effects of climate change in the Middle East (ME) region and the strategies suggested to combat its impacts. The research involves reviewing and analyzing published articles from major databases in this domain. The literature shows that countries in the ME region, with a particular focus on the Arab countries, have also realized that urgent actions should be taken to decrease climate change threats. Several countries are committing to international principles, supporting the global effort against climate change, such as adopting renewable sources for efficient energy production. Moreover, some of the ME region countries are considered a hub for emitting CO2 because of their hot climate, which requires the use of energy for air-conditioning, highwater desalination demands due to water scarcity, and the dependence on energy-exhaustive industries. Recently, Saudi Arabia, Qatar, and the United Arab Emirates have proposed strict measures to reduce their energy consumption and move towards renewable energy sources like solar and wind energy. Some countries have also funded projects for developing green buildings to create a sustainable environment. However, this paper emphasizes the need to establish strict regulations to impose policies and practices to achieve the global temperature rise limit below 1.5oC. Moreover, all ME countries must invest in renewable energy sources by promoting education, research, and implementing carbon pricing mechanisms. Nevertheless, as part of the Paris Agreement and other international commitments, there is a growing need to develop more socioeconomic policies to meet this vision.